2011
DOI: 10.1126/science.1203619
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Inactivation of STAG2 Causes Aneuploidy in Human Cancer

Abstract: Most cancer cells are characterized by aneuploidy, an abnormal number of chromosomes. We have identified a clue to the mechanistic origins of aneuploidy through integrative genomic analyses of human tumors. A diverse range of tumor types were found to harbor deletions or inactivating mutations of STAG2, a gene encoding a subunit of the cohesin complex, which regulates the separation of sister chromatids during cell division. Because STAG2 is on the X chromosome, its inactivation requires only a single mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
423
4
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(452 citation statements)
references
References 24 publications
19
423
4
2
Order By: Relevance
“…In contrast, in myeloid neoplasms, recurrent mutations and deletions have been detected in another study (Kon et al, 2013). Although there is dispute concerning the mutation of STAG2 in other carcinomas, it is reported by many scientists that there is a frequent mutation of STAG2 in bladder cancer (Solomon et al, 2011(Solomon et al, , 2013Balbás-Martínez et al, 2013). However, there is currently no evidence that shows whether loss of STAG2 leads to aneuploidy in bladder cells.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, in myeloid neoplasms, recurrent mutations and deletions have been detected in another study (Kon et al, 2013). Although there is dispute concerning the mutation of STAG2 in other carcinomas, it is reported by many scientists that there is a frequent mutation of STAG2 in bladder cancer (Solomon et al, 2011(Solomon et al, , 2013Balbás-Martínez et al, 2013). However, there is currently no evidence that shows whether loss of STAG2 leads to aneuploidy in bladder cells.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, SA2 has direct contacts with specific regions of the C-terminal end of CTCF, and all other cohesin components are recruited through their interaction with SA2 (Xiao et al, 2011). In 2011, Waldman's group showed that targeted inactivation of STAG2 led to chromatid cohesion defects and aneuploidy (Solomon et al, 2011). Subsequently, the loss of expression of STAG2 has been reported in colorectal, gastric and prostate carcinomas; however there are few mutations in STAG2 in these carcinomas .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a genome-wide analysis of distribution of SA1 and SA2 revealed a unique role of cohesin-SA1 in gene regulation, such as at the c-myc and protocadherin loci (Remeseiro et al 2012b). It has also been reported that targeted inactivation of SA2 in a human cell line causes cohesion defects and aneuploidy (Solomon et al 2011). In the future, it will be of importance to determine how cohesin-SA1 and -SA2 are targeted to specific loci at a mechanistic level, although there is evidence that SA1 might use its AT-hook motif for telomere binding (Bisht et al 2013).…”
Section: Cohesin Establishes Sister Chromatid Cohesion During S Phasementioning
confidence: 99%
“…These genes include the RTK pathway genes (Met, Nf1, and Pdgfrb) as well as previously undescribed genes, such as Stag2, Traf3, Dmxl1, Foxj3, and Faf1, which are the top five glioma-specific candidate cancer genes listed in Dataset S3. Stag2, a gene encoding a subunit of cohesin, plays essential roles in genomic instability (47). Traf3 is an adaptor protein that directly binds to a number of TNF receptors.…”
Section: Discussionmentioning
confidence: 99%